Coordination and Optimization: The Integrated Supply Chain Analysis with Non-Linear Price-Sensitive Demand - Mohammed Forhad UDDIN; Kazushi SANO (An International Journal of Optimization and Control: Theories & Applications, 2012)
In this paper, a supply chain with a coordination mechanism consisting of a single vendor and buyeris considered. Further, instead of a price sensitive linear or deterministic demand function, a price-sensitivenon-linear demand function is introduced. To find the inventory cost, penalty cost and transportation cost, it isassumed that the production and shipping functions of the vendor are continuously harmonized and occur at thesame rate. In this integrated supply chain, the Buyer’s Linear Program (LP), vendor’s Integer Program (IP) andcoordinated Mixed Integer Program (MIP) models are formulated. In this research, numerical example ispresented which includes the sensitivity of the key parameters to illustrate the models. The solution proceduresdemonstrate that the individual profit as well as joint profit could be increased by a coordination mechanismeven though the demand function is non-linear. In addition, the results illustrate that Buyer’s selling price, alongwith the consumers purchasing price, could be decreased, which may increase the demand of the end market.Finally, a conclusion